INSTITUTIONAL ASPECTS AND RISKS IN THE DIGITAL ECONOMY: WAYS TO REDUCE UNCERTAINTY FOR ECONOMIC AGENTS - Kurpayanidi Konstantin Ivanovich (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In the rapidly evolving landscape of the modern world, the inexorable shift towards a digital revolution is reshaping traditional economic models across the globe, including the Republic of Uzbekistan. This article delves into the impediments posed by institutional constraints in the digital economy, elucidating how legal frameworks governing digital interactions and inefficient institutional arrangements can impede the development and optimization of digital business models. Notably, the absence of clear regulations on electronic payments, cybersecurity, and data protection can introduce unpredictability, jeopardizing security and trust within the digital environment. The abundance of data and information, coupled with unequal distribution among market participants, may lead to suboptimal decision-making, inefficient resource utilization, and disparities in access to digital opportunities. The article aims to analyze and propose strategies to overcome institutional limitations and information asymmetry, emphasizing the need for effective institutional structures and mechanisms. In conclusion, this article provides a comprehensive examination of the challenges and opportunities in optimizing the digital economy in Uzbekistan. By proposing strategies to address institutional constraints and information asymmetry, it offers a roadmap for fostering a thriving digital ecosystem that benefits all stakeholders in the Republic of Uzbekistan.